FAKTOR-FAKTOR YANG MEMPENGARUHI BESARNYA PENGIRIMAN REMITAN KE DAERAH ASAL STUDI KASUS TENAGA KERJA MAGANG ASAL KABUPATEN JEMBRANA DI JEPANG - I Ketut Ardana; I Ketut Sudibia; I Gusti Ayu Putu Wirathi (PIRAMIDA, 2011)
Labor mobility for some people is one of the strategies of ruralhouseholds to improve economic conditions by improving their incomes. Thereason why the mobility Cenderungnya headed overseas, partly because of theeconomic conditions of the region of origin can not meet the needs of life insociety. Instead the country of destination is more promising in terms ofincreased revenue. Even with the income he earned at the destination, they areable to deliver remittances to the households left behind in the area of origin.This study aims to determine how the influence of income, consumptionexpenditure, number of family members in the area of origin, and thesimultaneous presence of parents or partially to the delivery of remittances tothe region of origin and to examine the use of sending remittances to theirhometown. The data used are primary data in a sample of 122 out of 177members of the population. Sampling was done by proportional stratifiedrandom sampling. Analysis technique used is multiple linear regression with theF test and t test.Results showed that, simultaneously income, consumption expenditure,number of family members in the area of origin and the presence of parentssignificantly influence the delivery of remittances to Fcount (64.957) > Ftable of(2.68). Partially, the income has positive and significant impact on delivery ofremittances to the region of origin. Consumption expenditure and a significantnegative effect on the delivery of remittances to the region of origin. Thenumber of family members and significant positive effect on the delivery ofremittances to the region of origin, while the presence of parents does notsignificantly influence the delivery of remittances to the region of origin.Sending remittances to family utilization in areas used for debt repayment,investment and home construction as well as in savings.